Utilization Of Eggshell Powder Waste As An Added Material To Mortar - R. Arco Hermawan Brahmassetyo; Nurul Rochmah (Student Scientific Creativity Journal, 2023)
In the development of increasingly developed technology and the demands of the community's needs for infrastructure facilities, it also affects the development of a construction field. This is also no exception in the manufacture of mortar which is used as a non-structural material in buildings. In making mortar itself, it is also influenced by developing technological developments, one of the types affected is pozzolan mortar. Pozzolan mortar has added materials derived from nature or industrial waste. In Indonesia, waste from eggshells is increasing every year, because eggshells are one of the people's favorite food ingredients. The eggshells have contain calcium carbonate (CaCO3) compound which is an element than cement. The materials of making the mortar itself are water, cement, and sand. This research aims to utilize egg shell waste as an added material in mortar with variations in the percentage of 0%, 5%, 10%, and 15% eggshell powder. From the results obtained, the addition of eggshell powder at maximum compressive strength lies at a percentage of 15% of 300 MPa.